The effect of section 11 of the natural wealth and resources (permanent sovereignty) act no 5 of 2017 on bilateral investment treaty protection in Tanzania - Gerber, Leonardus J. (University of Pretoria, 2024)
Min Dissertation (LLM (Extractive Industries Law in Africa))-- University of Pretoria, 2023.